Application of numerical simulation for the analysis of the dynamic behaviour of valve train systems. (4th August 2014) - Adam, M.; Bakaj, L.; Woyand, H.B.
A computer program is presented which allows the numerical analysis of the dynamic behaviour of finder follower valve train systems with alternative hydraulic or mechanical lash adjustment. The valve train is reduced to a discrete–oscillation model and described by a set of differential equations. The solution is found by an adaptive numerical integration method. The program has proved to be a powerful tool for the initial stage of product development or the concept phase, when no hardware or measurement results of the new valve train design are available. In addition, its ability to perform tasks such as fine tuning and optimisation of system parameters, and the revealing and assessment of malfunctions, make the program well suited to analysis at the final stage before and during mass–production. All comparisons of simulation and measurement results carried out so far reveal an acceptable correlation. Only the damping parameters had to be tuned on the basis of measured results. The analytical solution of the damping behaviour is one of the main topics of continuing investigations.